INTERPRETASI PENONTON TERHADAP PLURALISME DALAM FILM (Analisis Resepsi Interpretasi Penonton Terhadap Pluralisme Dalam Film Cin(T)a) - Dwi Mahliza Ulfa (FLOW, 2013)
This research is titled "Interpretation of the audience towards pluralism in the film Cin(T)a". Film Cin(T)a was launched on 2009, tells about the romance between two youths with different cultures and beliefs. This film raised a lot of pros and cons in public. This indie movie which filmed by Sammaria Simanjuntak, considered reviving the issue of pluralism after the MUI (Indonesian Ulama Council) gave haram fatwa in 2005. The scenes in film Cin(T)a present a unique overview about the differences between two characters who represent the majority and minority groups in Indonesia, and are packed with casual dialogues without conflict, but full of meanings. The aims of this research is to see how the audiences interpretation of pluralism that they watched in film Cin(T)a. The Method used in this research is qualitative method, using analysis reception stated by Stuart Hall about how audiences produces a message from a media text. This process will produce different meaning, influenced by the capacity of each audience. Data is obtained from in-depth interview with five informants with different backgrounds. The result showed that informants concluded film Cin(T)a as film which raised up the phenomenon of  diversity and plurality in Indonesia. In addition the film also tried to convey the message of pluralism and tolerance through scenes and dialogue in it. When produces the meaning of film Cin(T)a, differences in religious background, socio-cultural, and the experience of informants becomes an important factor that distinguishes their meaning. Keywords: Pluralism, Diversity, Plurality, Tolerance, Reception Analysis